A novel solar desalination system integrating inclined and tubular solar still with parabolic concentrator. (August 2022) - Ahmed, Mohamed M.Z.; Alshammari, Fuhaid; Alatawi, Ibrahim; Alhadri, Muapper; Elashmawy, Mohamed
Highlights: A novel system integrating inclined and tubular solar stills is developed. The developed device productivity and efficiency are 7.82 L/day and 35.62%. Freshwater production cost of the developed device is very competitive $0.012. Abstract: Nowadays, solar energy has great attention and attracts many researchers for cleaner production applications including direct solar energy utilization for water desalination. The present study introduces a novel solar desalination system integrating high temperature tubular solar still, heated by a parabolic concentrator solar tracking device, and a low temperature inclined solar still device. In this system a small circulation water pump was used to circulate saline water in both devices through a copper U-tube heat exchanger placed inside the trough of the tubular solar still. This strategy is expected to regulate the excessive heat of the tubular solar still exerted by the parabolic concentrator and increase the temperature inside the inclined solar still. Results showed high performance of the augmented system with a daily freshwater yield and thermal efficiency of 7.82 L/day and 35.6%, respectively. Furthermore, a low production cost per liter of $0.012 has been achieved. The developed system can comfortably secure the essential daily needs of one person which is suitable for low demand of isolated and small communities. The obtained results will open further development opportunities for future research efforts.